Paradoksy awangardowego zaangażowania. Ideologia (artystycznej) zmiany w powieści „Palę Paryż” Brunona Jasieńskiego - Boruszkowska, Iwona (Zagadnienia Rodzajów Literackich, 2019)
The article contains considerations about the political and ideological engagement of the avantgarde writer that were developing in the inter war period and which have their origins amongst, for example, avant-garde ideas. The paper analyses Bruno Jasieński’s text “Palę Paryż” (I burn Paris) (1931), while the context for the novel is a critical revision of the relationship between politics and literature.